Prevalence of Depression Among Medical Students Residing in Hostels of BMC Quetta - Lehri, Aamir Salam; Azam, Saima; Jabeen, Shaista; Mengal, Safia; Khan, Zain Ullah; Qadir, Abdul; Kakar, Sana Ullah (Biological and Clinical Sciences Research Journal, 2025)
Medical students, especially those living in hostels, face heightened risks for depression due to academic burdens, social isolation, and disrupted daily routines. Despite the growing recognition of mental health issues in educational settings, depression among this population remains underdiagnosed and inadequately addressed, particularly in developing countries. Objective: To determine the prevalence and severity of depression among hostel-residing medical students at Bolan Medical College (BMC), Quetta, using standardized psychological assessment tools. Methods: A descriptive cross-sectional study was conducted over two months (March to April 2025) among 250 hostel-residing undergraduate medical students at BMC Quetta. Participants were selected through convenience sampling. Depression levels were assessed using the Patient Health Questionnaire-9 (PHQ-9) and the Beck Depression Inventory-II (BDI-II). Demographic variables, including age, gender, and academic year, were recorded via a structured questionnaire. Data analysis was performed using SPSS version 25. Prevalence of depression was calculated based on PHQ-9 and BDI-II thresholds. Associations between depression and demographic variables were evaluated using chi-square tests, and logistic regression was employed to determine predictors of depression. A p-value of <0.05 was considered statistically significant. Results: Out of 250 participants, 54.8% (n=137) were female and 45.2% (n=113) were male. Using a PHQ-9 cutoff of ≥10, 28.8% (n=72) screened positive for at least moderate depression, whereas the BDI-II cutoff of ≥14 classified 51.6% (n=129) as depressed. Mild-to-moderate depression accounted for the majority of cases. Female students and those in the first and second academic years had significantly higher depression scores (p<0.05). A strong positive correlation (r = 0.82) was observed between PHQ-9 and BDI-II scores. Conclusion: A considerable proportion of hostel-residing medical students at BMC Quetta experience depressive symptoms, with younger and female students being more vulnerable. Regular mental health screenings and institutional support services are urgently needed to address this concerning trend and promote student well-being.